Phosphate precipitation as struvite from municipality wastewater - Ramaru, Rendani (Department of Chemical Engineering, 2014)
Tshwane Municipality produces approximately 4Ml/day of dewatering liquors arising from municipal sludge from a wastewater treatment plant. The sludge being dewatered is a combination of an anaerobically digested primary sludge and an undigested waste activated sludge. High phosphate and nitrogen are released into water during the anaerobic treatment process. High concentrations of these nutrients in the wastewater lead to eutrophication, which is a major environmental problem (Doyle et al., 2000). In view of the above problem, the aim of this project was to investigate the feasibility of precipitating phosphate in the form of struvite (MgNH4PO4.6H2O) from the Tshwane Municipality dewatering liquors and consequently recovering it as a valuable and marketable product. The project was investigated in three sequential stages consisting of: 1. An aqueous thermodynamic modelling study using OLI Systems Inc. Stream Analyser Version 2.0.57 to determine the precipitation conditions required for the removal of phosphates in the dewatering liquor. 2. Bench'scale laboratory experiments to investigate the feasibility of phosphate precipitation as struvite under different pH conditions, Mg: P molar ratios and Ca:P molar ratios. 3. Fluidised bed experiments to establish the characteristics of phosphate removal at varying levels of supersaturation. The results suggest that the pH of the system has a significant effect on phosphate removal due to its influence on the availability of PO4 3, NH4 + and Mg2+. According to the thermodynamic modelling results, phosphates are removed as Ca3(PO4)2 and Mg3(PO4)2.8H2O. Removal of phosphate as Mg3(PO4)2.8H2O starts at a pH above 7 with the maximum removal achieved at pH 10. Thereafter, phosphate removal as Mg3(PO4)3.8H2O drops to zero due to Mg(OH)2 precipitation being favoured at the higher pH values. Thermodynamic modelling shows that a high NH4 +:P molar ratio is required to induce struvite precipitation. For sample C1, which had a PO4 P and an NH4 + concentrations of 145mg/L and 65mg/L respectively, the bench scale experiments showed that approximately 30%, 80% and 92% of the phosphate was removed at pH 8, pH 9 and pH 10, respectively. The NH4 +:P molar ratio in ii the precipitate decreased to zero at pH 10 because NH3 formation is favoured at this pH. The XRD analysis showed that the precipitate was Mg3(PO)2.22H2O. On the other hand, it was shown that phosphate was removed as struvite, for sample C2, which had PO4 P and NH4 + concentrations of 93mg/L and 57 mg/L, respectively. The NH4 +: P molar ratio of sample C1 was 0.99 while the NH4 +: P molar ratio of sample C2 was 1.35. However, it was shown that phosphate was removed as Mg3(PO)2.22H2O under pH 10 conditions. Thus, high NH4 +: P molar ratios (i.e. 1.35) in the waste water favours struvite precipitation with the optimum pH level for phosphate removal as struvite being pH 9. Bench scale experiments showed that, amorphous calcium phosphate precipitation is favoured over struvite precipitation at high Ca:P molar ratios. At a Ca:P molar ratio of 0.85:1, it was shown that no struvite was formed. The bench scale experiments showed that the phosphate conversion increased at high Mg:P molar ratios. However, the effect of increasing Mg:P molar ratio on phosphate conversion was significant at pH 9. While at pH 10 there was insignificant increase of phosphate conversion as Mg:P molar ratio was increased probably due to formation of MgOH+ ions at high pH levels. It was shown that high Mg:P molar ratios slightly limits calcium conversion. The calcium conversion was reduced by approximately 10% when Mg: P was increased from 1:1 to 1.4:1 for systems operated at pH 9 and pH 10 conditions. The supersaturation ratio of amorphous calcium phosphate is 104 greater than the magnesium compounds (i.e. struvite and Mg3(PO4)2.22H2O) supersaturation ratio as a result the effect of increasing Mg:P on calcium conversion was relatively very small. The fluidized bed reactor experiments showed that high Mg:P molar ratios increased the phosphate removal as a result of the increased free Mg2+ concentration. However, the high Mg:P molar ratios resulted in an increased supersaturation which led to the formation of many fine particles. There was an increase in overall conversion from 68% to 83 % when the Mg:P molar ratio was increased from 1:1 to 1.2:1. On the other hand, the removal decreased from 45% to 38% when the Mg:P molar ratio was increased from 1:1 to 1.2:1. Moreover, struvite with high purity was produced at a high Mg:P molar ratios (i.e. Mg:P =1.2). Fluidized bed reactor experiments showed that as the recycle ratio was increased the PO4 P conversion also increased. Thus, large amount of struvite particles were recycled to the fluidized bed reactor. As a result, struvite particles provide favourable nucleation sites for struvite precipitation hence high conversion were achieved at higher recycle ratio.